ÁLVARES, Maria Manuela e ÁLVARES, José (2020), Novos Ensaios Luso-Nipónicos, Chiado Books. ISBN: 978-989-52-6607-4, 148 pp. - Silva, Armando Malheiro da (História: revista da Faculdade de Letras da Universidade do Porto, 2022)
ÁLVARES, Maria Manuela e ÁLVARES, José (2020), Novos Ensaios Luso-Nipónicos, Chiado Books. ISBN: 978-989-52-6607-4, 148 pp. (13 €)